Cooperative trajectory prediction system for intelligent and automated connected convoy based on blockchain - Rensheng WANG; Tianhao WU; Lin ZHANG; Konglin ZHU (网络与信息安全学报)
Autonomous vehicles have been extensively researched and developed rapidly in recent years.However,these vehicles may be not able to avoid collision with vehicles that appear suddenly.To solve this problem,a cooperative trajectory prediction system for intelligent and automated connected convoy based on blockchain was proposed.In the proposed system,each node in the intelligent and automated connected convoy and roadside infrastructure predict the trajectory of vehicles around them with the LSTM model,and they share the information they get.Using blockchain,the intelligent and automated connected convoy and roadside infrastructure rate the received messages.The summarized rating will be stored as a block in the blockchain that stores the trust values.Vehicles in the intelligent and automated connected convoy are able to judge whether the other nodes in the Conroy are credible according to their trust value,and messages from the low trust value sender will be ignored,thus achieving cooperative driving.Experiment shows that the proposed system plays a significant role in improving driving safety of the intelligent connected platoon.